Castleman s disease (A giant lymph node hyperplasia at supraclavicular region) - K.Alac, S.Nilgun; Guler, Z.Mujgan; Arab Ibrahim Kilic, H.Canan; Alban, S.Tamer (Annals of Medical Research, 2021)
None
Keywords: s: Lymph node hyperplasia, Castleman's disease